2018
DOI: 10.1021/acs.jctc.8b00685
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Relative Binding Affinity Using Nonequilibrium QM/MM Simulations

Abstract: Calculating binding free energies with quantum mechanical (QM) methods is notoriously time consuming. In this work, we study whether such calculations can be accelerated by using non-equilibrium (NE) molecular dynamics simulations employing Jarzynski's equality. We study the binding of nine cyclic carboxylate ligands to the octa-acid deep-cavity host from the SAMPL4 challenge with the reference-potential approach. The binding free energies were first calculated at the molecular-mechanics (MM) level with free-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 72 publications
2
39
0
2
Order By: Relevance
“…This gave even better results with a precision of 0.5-0.9 kJ/mol, a MAD of 4.7 ± 0.2 and a R 2 correlation of 0.86 ± 0.04. Recently, we have shown that similar results can be obtained with approximately a fourth of the computational effort using multiple short QM/MM simulations [23] or by using non-equilibrium simulations and Jarzynski's equality [32][33][34].…”
Section: Introductionsupporting
confidence: 58%
“…This gave even better results with a precision of 0.5-0.9 kJ/mol, a MAD of 4.7 ± 0.2 and a R 2 correlation of 0.86 ± 0.04. Recently, we have shown that similar results can be obtained with approximately a fourth of the computational effort using multiple short QM/MM simulations [23] or by using non-equilibrium simulations and Jarzynski's equality [32][33][34].…”
Section: Introductionsupporting
confidence: 58%
“…This is suggestive that computational resources could be better utilized by repeating many, short simulations from different starting positions rather than performing extended sampling of a single simulation, as is done here. 61,62…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of all methods often did not significantly improve upon extending the simulation sampling from 50 ps to 200 ps, which suggests that computational resources could be better utilized by reperforming short simulations several times and averaging the results. 61,62…”
Section: Discussionmentioning
confidence: 99%
“…25 We have also developed two approaches to speed up the RPQS approach using either multiple short equilibrium or non-equilibrium MD simulations. 26,27 It is well-known that SQM methods are less reliable than DFT methods for intermolecular interactions and binding affinities. 28,29 Therefore, it is of great interest to develop methods to obtain relative binding free energies at the DFT level of theory.…”
Section: Introductionmentioning
confidence: 99%